PERILAKU PETANI TERHADAP RISIKO USAHATANI KEDELAI DI KECAMATAN JAWAI SELATAN KABUPATEN SAMBAS - KURNIATI, DEWI (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2015)
This research aimed determine the effect of production factors on the soybean productivity and determine the behavior of farmers towards risk of soybean farming. The research areas is in Sambas District subdistrict of Jawai Selatan. The village sample selected is Sarang Burung Kolam Village with Â 31 farmers. Analysis of the behavior of farmers toward risk refers to the method Moscardi and de Janvry (1977). Production function used in this study to determine the value of risk aversion parameter or K(S) is a productivity function. The results of productivity functions using SPSS software. Seed, NPK, Urea, insecticides and labor significant effect on soybean productivity. While herbicide did not significantly effect on soybean productivity. The behavior of farmers towards risks are Risk Neutral 48.39% of farmers.Â Key Words: Behavior, Risk, Production Function, Soybean Farming